Zmiana kultury konsumpcyjnej - wyzwanie dla zarządzania - Sułkowski, Łukasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The purpose of the paper is the diagnosis of the transition process from the stage of the modernist consumer culture to the stage of post-modernist consumer culture and the description of the implication of this change for management. The culture of post-modernist consumptionism that was shaped in the second half of the 20th and at the beginning of the 21st century and dominates nowadays is significantly different from preceding modernist culture. It is mostly connected with the development of the global market, growth of the competitive tension and culture based on new forms of communication. Consumers are subject to the pressure of mass culture and cultural industry which shape their identity. Taking actions in the conditions of the new cultural formation poses new challenges for enterprises producing and selling market goods to consumers. They change strategies, structures, corporate cultures as well as all functional spheres. The deepest change concerns creating flexible strategies oriented towards building positive market image of brands, development of information management systems and marketing of identity and relations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 393-398